Traditional healers and management of HIV/AIDS cases at a university in Zimbabwe - Matunhu, Viola; Matunhu, Jephias (Midlands State University, 2015)
Development aims to improve human life. Several challenges have militated against world development; HIV and AIDS are some of the major factors to consider in the discourse of development. The disease has since reached epidemic and pandemic levels. Africa, one of the least developed continents on earth is the hardest hit by the pandemic. According to westerners, there is no cure for HIV/AIDS. However, some traditional healers and faith healers claim that HIV/AIDS are curable. The study investigated the influence of traditional healers in the management of the epidemic in a university in Zimbabwe. This transcendental phenomenology collected data from people with lived experience of the phenomenon under investigation. Data were collected from HIV positive university students and staff, and traditional healers who have lived experiences of managing HIV/AIDS patients. The study established that traditional healers have a significant influence on HIV/AIDS positive students and staff at the university. Government of Zimbabwe should incorporate traditional healers in its HIV/AIDS strategic plans.